Penyelesaian Sengketa Konsumen Mengenai Penjualan Wafer Cheese Nabati Kadaluwarsa Di Toserba Asia Garut Ditinjau Dari Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Diva Yohana Margaretha Marbun; Aam Suryamah; Agus Suwandono (Concept: Journal of Social Humanities and Education, 2023)
The position of business actors and consumers often becomes unequal. Consumers are often the object of business activity to get the maximum profit by business actors and in the end the consumer becomes the aggrieved party. Cases of business actors harming consumers are found in BPSK Garut Regency Decision Number 18/Pdt.S-Brg/BPSK-GRT/IX/2020 regarding the sale of expired vegetable cheese wafers at the Asia Garut Department Store. In this case, there were legal issues regarding BPSK's authority and the judge's considerations in deciding compensation. The research objective is to determine whether BPSK has the authority to decide this case; and analyzing the judges' considerations in the BPSK Decision of Garut Regency Number 18/Pdt.S-Brg/BPSK-GRT/IX/2020 in deciding compensation. This study uses research methods with a normative juridical approach based on applicable legal concepts and theories. Based on the research results, it can be concluded 2 (two) things. First, the settlement process in this case has not provided legal certainty because the choice of dispute resolution method is directly determined by the Garut Regency BPSK Assembly and not based on the agreement of the parties to the dispute and this case should have been tried at the District Court after mediation failed. Second, the Garut Regency BSPK Assembly has not been right in deciding on compensation because the Assembly has confused the duties and responsibilities of producers and supermarkets and does not understand the intent of Article 52 letter (k) of the Consumer Protection Act.